Reactivity of fluorinated organic radicals in aqueous media - Barata Vallejo, Sebastian (2012)
Fluorinated radicals in water are shown to enable a useful array of synthetic organic transformations, reflecting these intermediates' distinct behavior in water or aqueous media. The enhanced reactivities of perfluroalkyl radicals in water facilitate their addition reactions to carbon–carbon and carbon–heteroatom multiple bonds. Activated and unactivated unsaturated substrates are equally reactive candidates for radical perfluoroalkylation reactions in aqueous systems. Parallel behavior of perfluorinated radicals in organic solvents and in water is presented, demonstrating the scope of reactions based on fluorinated radicals in aqueous media, as well as the ease of carbocyclic construction.